2012
DOI: 10.1037/a0028187
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of protective behavioral strategies: Comparing prediction and factor structures across measures.

Abstract: Protective behavioral strategies (PBS), or drinking control strategies, are specific behaviors one can utilize to minimize the harmful consequences of alcohol consumption. As there is not currently a standard measure of PBS, the goal of the present study was to examine the factor structure and concurrent validity of three scales designed to assess PBS: Protective Behavioral Strategies Scale (PBSS; Martens, M. P., Ferrier, A. G., Sheehy, M. J., Corbett, K., Anderson, D. A., & Simmons, A., 2005 Development of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(111 citation statements)
references
References 40 publications
10
99
2
Order By: Relevance
“…Although multiple studies have confirmed the three-factor structure of the PBSS (e.g., Martens et al, 2007b;Pearson et al, 2012a), some researchers have found support for a twofactor (Madson et al, 2013) or four-factor solution (Walters et al, 2007). Although we know of no studies finding a singlefactor solution for the PBSS, each of the studies reviewed above used either a single total score or latent variable with PBSS subscales as indicators, which again could obfuscate the true relationships among PBS use and alcohol outcomes.…”
Section: Overall Discussionmentioning
confidence: 99%
“…Although multiple studies have confirmed the three-factor structure of the PBSS (e.g., Martens et al, 2007b;Pearson et al, 2012a), some researchers have found support for a twofactor (Madson et al, 2013) or four-factor solution (Walters et al, 2007). Although we know of no studies finding a singlefactor solution for the PBSS, each of the studies reviewed above used either a single total score or latent variable with PBSS subscales as indicators, which again could obfuscate the true relationships among PBS use and alcohol outcomes.…”
Section: Overall Discussionmentioning
confidence: 99%
“…A growing body of literature suggests that different types of PBS may not be equally useful for reducing alcohol risk (Napper, Kenney, Lac, Lewis, & LaBrie, 2014). For example, strategies aimed at avoiding consequences or changing the way a student drinks are more closely related to less drinking and consequences than strategies that involve stopping or limiting drinking (Frank, Thake, & Davis, 2012; Napper et al, 2014; Pearson, Kite, & Henson, 2012, 2012). In the current study, intervention students reported the greatest increases in stopping or limiting drinking PBS, rather than strategies more closely related to reductions in alcohol risk.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to counterintuitive associations with alcohol use and problems (e.g., positive, curvilinear, or nonsignificant relationships). The inconsistent relationship between PBS and alcohol use has been observed repeatedly with the SQ (Kite et al, 2013; Pearson et al, 2012; Sugarman & Carey, 2007, 2009) as well as other scales (Kite et al, 2013; Werch, 1990). …”
Section: Inconsistent Pbs Relationships and Response Scalesmentioning
confidence: 92%